An Improved State Equation in the Vicinity of the Critical Point - Verbeke, Olav B. (J Res Natl Bur Stand A Phys Chem, 1972)
An improved state equation for the vicinity of the critical point is proposed. An analysis of the experimental data on helium and xenon has been carried out in order to investigate the influence of the number of constants in the equation and the PρT range on the critical constants T(c) and ρ(c) and on the critical exponents α, β, γ, and δ. No such influence has been detected. The model for the critical point, recently proposed by Widom. has been checked regarding its consequences for the rectilinear diameter. No definite confirmation but indications for its correctness have been found.